Does fasting plasma glucose values 5.1-5.6 mmol/l in the first trimester of gestation a matter? - Ramezani Tehrani, Fahimeh; Farzadfar, Farshad; Hosseinpanah, Farhad; Rahmati, Maryam; Firouzi, Faegheh; Abedini, Mehrandokht; Hadaegh, Farzad; Valizadeh, Majid; Torkestani, Farahnaz; Khalili, Davood; Solaymani-Dodaran, Masoud; Bidhendi-Yarandi, Razieh; et al. (Frontiers in Endocrinology, 2023)
Objectives The aim of the study was to investigate the effect of treatment on pregnancy outcomes among women who had fasting plasma glucose (FPG) 5.1-5.6 mmol/l in the first trimester of pregnancy. Methods We performed a secondary-analysis of a randomized community non-inferiority trial of gestational diabetes mellitus (GDM) screening. All pregnant women with FPG values range 5.1-5.6 mmol/l in the first trimester of gestation were included in the present study (n=3297) and classified to either the (i) intervention group who received treatment for GDM along with usual prenatal care (n=1,198), (ii) control group who received usual-prenatal-care (n=2,099). Macrosomia/large for gestational age (LGA) and primary cesarean-section (C-S) were considered as primary-outcomes. A modified-Poisson-regression for binary outcome data with a log link function and robust error variance was used to RR (95%CI) for the associations between GDM status and incidence of pregnancy outcomes. Results The mean maternal age and BMI of pregnant women in both study groups were similar. There were no statistically significant differences in the adjusted risks of adverse pregnancy outcomes, including macrosomia, primary C-S, preterm birth, hyperbilirubinemia, preeclampsia, NICU-admission, birth trauma, and LBW both groups. Conclusions It is found that treating women with first-trimester FPG values of 5.1-5.6 mmol/l could not improve adverse pregnancy outcomes including macrosomia, Primary C-S, Preterm birth, hypoglycemia, hypocalcemia, preeclampsia, NICU admission, Birth trauma and LBW. Therefore, extrapolating the FPG cut-off point of the second trimester to the first –which has been proposed by the IADPSG, might therefore not be appropriate. Clinical Trial Registration https://www.irct.ir/trial/518, identifier IRCT138707081281N1.